Villages of Heterosexual Desires: Practices, Discourses, and Customer Demographics at Filipina Hostess Pubs in Postcolonial Singapore (Asian Journal of Social Science Studies, 2023)
This article explores the author‟s observations, over the 2010-2019 period, at a sample of eight (8) Singapore hostess bars/pubs. The research method is participant-observation of practices, discourses, pricing models and customer demographics, backed up by knowledge gained from conversations with hostesses, bar managers, customers and musicians. It explains how surplus-value is extracted in the production process via the high prices of ladies‟ drinks, the hard work required because of the quota system (in relation to ladies‟ drinks), the high prices of customers‟ drinks (to a lesser extent) and long working hours. The article explains how alienation is involved in delivering heavily racialized and gendered services in an atmosphere where commissions and quotas on ladies‟ drinks put pressures and constraints on hostess‟s behaviour. Unruly and disrespectful customer conduct is another source of alienation, guilt and sadness for hostesses who are under pressure to act and talk in a (hetero)sexualized way. Subjects: business ethics, critical management studies, human geography, anthropology, marketing